Saxitoxin and tetrodotoxin bioavailability increases in future oceans - Roggatz, C. C.; Fletcher, N.; Benoit, D. M.; Algar, A. C.; Doroff, A.; Wright, B.; Wollenberg Valero, K. C.; Hardege, J. D. (Nature Climate Change, 2019)
© 2019, The Author(s), under exclusive licence to Springer Nature Limited. Increasing atmospheric CO2 levels are largely absorbed by the ocean, decreasing surface water pH1. In combination with increasing ocean temperatures, these changes have been identified as a major sustainability threat to future marine life2. Interactions between marine organisms are known to depend on biomolecules, although the influence of oceanic pH on their bioavailability and functionality remains unexplored. Here we show that global change substantially impacts two ecological keystone molecules3 in the ocean, the paralytic neurotoxins saxitoxin and tetrodotoxin. Increasing temperatures and declining pH increase the abundance of their toxic forms in the water. Our geospatial global model predicts where this increased toxicity could intensify the devastating impact of harmful algal blooms, for example through an increased incidence of paralytic shellfish poisoning. Calculations of future saxitoxin toxicity levels in Alaskan clams, Saxidomus gigantea, show critical exceedance of limits safe for consumption. Our findings for saxitoxin and tetrodotoxin exemplify potential consequences of changing pH and temperature on chemicals dissolved in the sea. This reveals major implications not only for ecotoxicology, but also for chemical signals that mediate species interactions such as foraging, reproduction or predation in the ocean, with unexplored consequences for ecosystem stability and ecosystem services.
Keywords: Climate-change ecology; Ecological modelling; Environmental chemistry